Features of microelement maintenance in rat's brain tissues at experimental hypoxia of different degree. - Tarasova I.V. (Морфологія, 2011)
Features of microelement maintenance (iron, zinc, copper, manganese, and cobalt), conditionally toxic chrome and toxic lead were studied in newborn rat's brain tissues at experimental hypoxia of different degree. Tissues of newborn rat’s brain are characterized by high level of saturation and considerable dynamism of microelement maintenance. Till the end of the first week of life, the maintenance of these microelements decreases in 1,5 – 10 times. The level of the toxic lead decreases more than in 2,5 times. The hypoxia of easy degree of newborn rats invokes reduction cobalt level 3 times, iron level 2 times, manganese – on 27,65 %, chrome – on 25,84%, zinc – on 16,43%. It means that considerable deficiency and disbalance of microelement maintenance rat's brain tissues. The heavy degree of hypoxia is characterized by further increase of deficiency and disbalance of microelements.